Analisis Afiks Pada Lirik Lagu Anggi Marito Dalam Album Tak Segampang Itu - Syahbana, Sultan Ali; Siagian, Irwan (Jurnal Ilmiah Wahana Pendidikan, 2023)
The purpose of this study is to explain the use of affixes in the lyrics of 'Anggi Marito' in the album 'Tak Segampang Itu'. The aim of this study is to improve our understanding of fixation. This study was carried out by qualitative method. The subject of this investigation was the use of affixes in the lyrics of "Anggi Marito" from the album "Tak Segampang Itu". Research data comes in the form of an obsession with Anggi Marito's lyrics on the Tak Segampang Itu album. The data sources for this study were written data in the form of lyrics to the song "Tak Segampang Itu" by Anggi Marito and speech data in the form of MP3 songs by "Tak Segampang Itu" by Anggi Marito. The data collection techniques used in this study were note-taking and listening. Affixing is the process of adding both singular and complex affixes form to form new words. Suffixes are divided into prefixes, infixes, suffixes and affixes. The prefix mi- forms both transitive and intransitive verbs. Noun forming functions and - were added. The ending -kan does not act as a word builder, it acts as a word builder.